Improving Self-Regulated Learning Skills of Students with Special Needs: Strategies and Outcomes - Sartinah, Endang Pudjiastuti; Purwoko, Budi; Wahyuni, Esa Nur; Irmawati, Ninin; Budiati, Eryana Fatimasari Retno; Oktafiolita, Anggraini (KONSELOR, 2024)
Inclusive education seeks to ensure fair access to quality education for kids with special needs, as stipulated by Law Number 20 of 2003 on The National Education System of Indonesia. Nonetheless, children with impairments frequently face obstacles in social interactions and academic pursuits. This study investigates the efficacy of Self-Regulated Learning (SRL) training in improving the socialisation skills of students with disabilities at SMA Negeri 3 Bondowoso, an inclusive institution. The study employed a quasi-experimental approach and included three students with distinct needs: a slow learner, a visually challenged student, and a student with speech difficulties. Over a period of four months, SRL training was executed, integrating individualised counselling to enhance participants' metacognitive, motivational, and behavioural competencies. Data were gathered by pretest-posttest assessments, follow-up evaluations, questionnaires, and interviews with students, educators, and parents. The results demonstrated substantial enhancements in socialisation abilities, with all participants attaining elevated levels of social engagement, communication, and emotional control following the intervention. The SRL framework, based on self-regulation and social cognitive theories, allowed students to reflect on their behaviours, adjust social strategies, and control emotions proficiently. Personal counselling enhanced their self-assurance and development. This study shows that self-regulated learning (SRL) training, in conjunction with counselling, is an effective intervention for enhancing social skills and independence in students with impairments. The findings enhance inclusive education practices, providing educators with a systematic method to tackle social issues and foster a supportive learning environment for all children.